Evaluation of satisfaction with over-the-counter weight loss supplements - Demirbağ Kaplan, Melike; Kasnakoğlu Tarı, Berna; Yiğitbaşı, Türkan; Kaplan, Yusuf Cem (My University, 2013)
Majority of studies on satisfaction with medication examine satisfaction with a prescribed pharmaceutical agent, while exploration of satisfaction with over-The-counter drugs is limited. This study aims to examine satisfaction with non-prescribed weight loss supplements and the factors that may affect satisfaction levels, such as overall body satisfaction. The participants in this study consisted of a convenience sample of 119 subjects who have either used weight loss supplement or are still using it at the time of enrollment. Results indicate that perceived effectiveness of weight loss supplement is the ultimate predictor of global satisfaction. Overall assessment of weight loss supplement revealed low satisfaction levels with regard to effectiveness and global satisfaction, while satisfaction with side-effects and convenience were relatively high. Body dissatisfaction was found to be significantly negatively correlated to satisfaction with effectiveness, side-effects and global satisfaction with weight loss supplement. Moreover, subjects with higher body dissatisfaction have a higher expectancy from weight loss supplement.
Keywords: Body Image; Dietary Supplements; Over-The-Counter; Pharmaceuticals; Satisfaction